2(x-3)-3(x+5)=3(x-2)-7?



Answers:
(2x-6)-(3x-15)=(3x-6)-7
x-9=3x-13
-2x=4 (-1)
2x=-4
x=-4/2
x=-2 :D
You need to solve both sides to get the answer obviously. You will have to distribute the 2 to the x and the -3 in the 1st parenthesis, and the -3 to the x and +5, then do the same on the other side. Then combine terms and see what comes up!

Good luck! (but watch your signs!)
x = -4/3
its been a while since ive done any math but I believe this is it
Answer is -2

2(x-3)-3(x+5)=3(x-2)-7
(2x-6)+(-3x-15)=3x-6-7
2x-3x-6-15=3x-13
-x-21=3x-13
-x-3x=-13+21
-4x=8
x=8/-4
x=-2
Remember always to plug your answer back in to the original problem to see if it will work.
the answer is -2
you go by the principle of BODMAS
Brackets
Of
Division
&
Multiplication
Addition
Sustraction

This article contents is post by this website user, EduQnA.com doesn't promise its accuracy.



More Questions & Answers...
  • What's some creative ways to say hello?
  • Anyone know the origin of 'Hell's Bells and Liberty Horses'. It was one of my dad's frequent expletives.
  • Find the error...is it impossible?
  • How do these words differ?
  • Can you unscramble these words for me please?
  • Does anyone else besides me think that this would be more of a.?
  • Who is a guru?
  • What's the one word you love your partner saying?
  • Copyright 2006-2009 EduQnA.com All Rights Reserved.